LOOP : our cicular economy inspirtion game that guides you in exploriing opportunities in the circular economy - Switchrs (Mechelen : Switchrs)
Loop is a card deck that can guide you in exploring opportunities in the circular economy. This innovation tool is a must have for professionals who want to design new business models, products and services with a circular economy mindset. The Tool is perfect to help you during the ideation phase at the start of a new project or when you want to make a certain product or service more sustainable.
Didactisch materiaal
Keywords: Educatieve spellen; Gezelschapspellen